Precise detection of a murine germline mutation of the Notch3 gene associated with kyphosis and developmental disorders - Torres, Haydee M; Antunes, Tania Rodezno; VanCleave, Ashley; Cao, Yuxia; Callahan, Dakota L; Westendorf, Jennifer J; Tao, Jianning (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Humpback (hpbk) mice harbor a pathogenic mutation in the Notch3 gene and can serve as a beneficial animal model for investigating human myopathy, kyphosis, and developmental disorders, including lateral meningocele syndrome. Detection of the point mutation in hpbk mice is important for maintaining strains and scrutinizing genetic rescues, especially considering that homozygous mice are infertile and indistinguishable from their littermates at a young age. This study aimed for the development of a novel, precise, and time-saving genotyping method to identify the mutation in hpbk mice. Materials and Methods: In order to study the hpbk mouse line, we describe how we applied several tools, including quantitative polymerase chain reaction (qPCR), multiplex tetra-primer amplification-refractory mutation system (ARMS-PCR) and Sanger sequencing, toward the recognition of heterozygous and homozygous mice. Results: The Notch3 mutation was clearly identified using qPCR and ARMS assays, but the latter was a more precise and cost-effective approach. The lengths of the ARMS-PCR amplicons are 210 bp and 164 bp for the wild-type and hpbk alleles, respectively. Moreover, the genotyping results for each mouse were corroborated by Sanger DNA sequencing. Conclusion: Our newly developed PCR-based ARMS system affords a swift and precise way to genotype the hpbk mice. ARMS-PCR does not rely on any advanced equipment and is useful as a genotyping method for other model organisms that harbor a pathogenic variant. J. Adv. Vet. Anim. Res., 8(1): 7-13, Mar 2021 http://doi.org/10.5455/javar.2021.h479